The effectiveness of strategic management of sports facilities in achieving the goals of physical education and sports for adolescent youth at the level of sports directorate structures. - Sedrati, Habib (sports creativity, 2025)
In the modern era, sports have become more important than ever before, to the point that they have become one of the criteria by which the progress and civilization of countries are measured. This is because they have imposed themselves through their positive and effective impact on their practitioners, men and women, young and old, healthy and sick. This has led to them being known as both a science and an art at the same time. Some have defined them as an integrated service system with its own mechanisms of operation, specific goals that we hope for, and clear purposes that it seeks. Sports, as a fertile field rich in various sports activities and events, gives the individual an opportunity to showcase their abilities and potential. Because sports encompass multiple fields, they invite everyone to practice them, as every individual will find the appropriate field for their abilities and needs. Sports include recreational sports for everyone without exception, elite sports for champions and professionals, therapeutic sports for the sick, adapted sports for the disabled, and school sports for those in educational institutions. Through this, the general question was as follows: - How effective is the management of sports facilities and resources in achieving some of the goals of physical education and sports? The researcher used the descriptive approach with a survey method, through a questionnaire directed to officials and employees of the Directorate of Sports in Bordj Bou Arreridj and Algiers, who constituted the research sample and were selected intentionally.